THE IMPACT OF FINANCIAL LITERACY ON STOCK MARKET PARTICIPATION - Parengkuan, Samuel Ray Aditya; Kim, Sung Suk (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This paper addresses the relationship between financial literacy and stock market participation and aims to reveal how an individual’s level of financial literacy affects stock market participation. Our comprehensive survey to measure financial literacy and investment behavior includes an assessment of financial literacy and investment attitudes. Results show that financial literacy has a significant impact on stock market participation, as individuals with high financial literacy better understand investment returns and make more informed decisions when making long- term investment is shown. Importantly, the results demonstrates that financial literacy is important in reducing ignorance about expected returns, effectively managing risk, and thereby preventing investors from engaging in optimistic investment behavior. This highlights the important role played by these findings highlight the potential of improving financial literacy to help investors make informed decisions and improve overall financial outcomes. The implications extend to policymakers, financial institutions, educators and individual investors, requiring a concerted effort to improve financial literacy for a more enlightened and responsible investment community.